Chimpanzees and human evolution - Muller, Martin N., 1971-; Wrangham, Richard W., 1948-; Pilbeam, David R. (The Belknap Press of Harvard University Press, 2017)
Although chimpanzees and other primates are frequently used as models to reconstruct the behavior of extinct human ancestors, this is rarely done in a consistent or methodologically rigorous fashion. This volume brings together leading scholars to explore how knowledge about chimpanzees can be used to understand both what is unique about our own species, and how these traits evolved. The first part of the book makes the case that the last common ancestor of chimpanzees and humans was chimpanzee-like. This inference is based not on an assumption that chimpanzees are a model species, but on morphological, developmental, and genetic data, together with evidence from the hominin fossil record. The second part of the book provides the first detailed record of the similarities and differences between humans and chimpanzees, including those in social system, mating system, diet, social behavior, hunting, tool use, culture, cognition, and communication.--